Pleurotus Species as source of nutraceuticals including vitamin B12 and lignocellulosic degradative enzyme - Patel, Yashvant; Prakash, 2. Anand Prakash; Patel, Ankit; Vishwakarma, Sanjay (Journal of BioScience and Biotechnology, 2020)
In the present study, we collected Pleurotus isolates from diverse edaphic zones from the parts of Uttar Pradesh. Neutraceuticals (proteins, carbohydrates, phenolic, vitamin B12) and xenobiotics degradation capacity of textile dyes along with the production of laccase enzyme evaluated. Isolate no. 06 appeared most distant in the dendrogram showing the highest MG degradation capacity, however, others showed excellent degradation of BPB. The laccase enzyme activity was found in the range of 4.03 to 19.13 IU/ml from mycelia extract. Gene frequency within isolates from 0.012 to 0.987 was analyzed through RAPD and the average gene diversity for all loci was 0.244 and the Shannon Information Index was found 0.397. The unbiased genetic similarity among isolates was 0.36 to 0.93 with a mean of 0.64. Significant genetic diversity, nutraceuticals and laccase enzyme availability and dye degradation capacity of the studied genus Pleurotus, was found, which makes it necessary to carry out a selection process in each one for superior selection not only for human being but also many aquatic as well as other terrestrial flora and fauna. The present investigation first time reported that Pleurotus species as a source of vitamin B12 in range of 0.05 to 0.32 mg/kg (of dried mushroom).